(untitled) (Ustozlar uchun, 2026)
This article examines the application of Task-Based Learning (TBL) activities in fostering speaking fluency among English as a Foreign Language (EFL) learners. Through a review of recent literature, experimental findings, and qualitative insights, it evaluates the effectiveness of TBL, highlights key techniques, and provides recommendations for educators and researchers. The article concludes with methodological guidance for producing publishable academic work in this domain.